2014
DOI: 10.1016/j.anireprosci.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Refrigerated storage of ram sperm in presence of Trolox and GSH antioxidants: Effect of temperature, extender and storage time

Abstract: Antioxidants have a potential to improve the quality and fertility of refrigerated-stored ram semen. Reduced glutathione (GSH) and Trolox (0.2, 1 and 5mM) were evaluated in ram semen preserved at 15 and 5°C up to 48 and 96h, respectively. Extenders were also evaluated (15°C: Tris-citrate-fructose, TCF, without lipids, and TES-Tris-fructose 10% egg yolk, TTF-EY; 5°C: TTF-EY and 3.5% soybean lecithin, TTF-SL; INRA96 at both temperatures). Storage at 5°C resulted in poorer quality than 15°C up to 48h, while allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
3
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 49 publications
2
29
3
4
Order By: Relevance
“…However, lower sperm motility and metabolism could be associated with pH reduction due to bacterial contamination and metabolite production (Yániz, Mateos, & Santolaria, ). Previous studies reported that 15°C is the optimal temperature to maintain a good percentage of motile cells and a high motility score during short‐term storage (Upreti, Oliver, Munday, & Smith, ), while the storage of semen at 5°C is clearly advantageous for long‐term storage (Mata‐Campuzano et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, lower sperm motility and metabolism could be associated with pH reduction due to bacterial contamination and metabolite production (Yániz, Mateos, & Santolaria, ). Previous studies reported that 15°C is the optimal temperature to maintain a good percentage of motile cells and a high motility score during short‐term storage (Upreti, Oliver, Munday, & Smith, ), while the storage of semen at 5°C is clearly advantageous for long‐term storage (Mata‐Campuzano et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the implementation of this technique in ovine is far away that which occurs in bovine or porcine. In order to explain the slow development of this technique in ovine, it can be argued the low economical profitability of these farms, the high variability of the fertility rates or the loss of sperm quality associated with cryopreservation or cooling process (Mata‐Campuzano et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies 1619, 34 have shown the beneficial effect of antioxidant therapy on the oxidative stress of mammalian spermatozoa. The addition of antioxidants has important benefits on the quality and fertility of ram semen after liquid storage at different temperatures 35 . To date, there have not been studies focus on determine the antioxidant effect on freeze dried sperm.…”
Section: Discussionmentioning
confidence: 99%
“…The female size, low economic return, variable fertility rates, and more rapid loss of semen quality with storage time are important obstacles for the routine use of these techniques. Therefore, sperm quality, which is negatively affected by cryopreservation, has a critical impact on the application of AI (Mata-Campuzano et al, 2014;Najafi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%